Photocatalytical properties of NiO nanofilms doped with Ba. (2nd June 2020) - Boulila, S.; Ghamnia, M.; Boukhachem, A.; Ouhaibi, A.; Chakhoum, M. A.; Fauquet, C.; Heresanu, V.; Tonneau, D.
ABSTRACT: We report on the photocatalytical properties of pure and barium-doped nickel oxide nanofilms synthesised on glass substrates using a simple spray pyrolysis method. The nanofilms were prepared from different solution concentrations obtained from pure nickel chloride hexahydrate (NiCl2 :6H2 O) powder in distilled water. Doping has been obtained at various concentrations of barium (0–5%) by simultaneously dissolving (BaCl2 :2H2 O) in the distilled water. The structure and the morphology of the NiO and Ba-NiO nanofilms were investigated by means of X-ray diffraction and atomic force microscopy. The observed principal (111), (200) and (220) XRD patterns peaks correspond to cubic NiO adopting the NaCl-type structure. AFM observations revealed a textured and rough surface. Optical reflectance and transmittance measurements showed an optical band gap corresponding to that of NiO, only slightly affected by the barium doping. The photocatalytic properties of the films were enhanced by barium doping as revealed by the degradation of methylene blue (MB) aqueous solution under ultraviolet irradiation. Between 70–80% of MB was consumed after 300 min ultraviolet irradiation with the addition NiO with Ba concentrations in the range 0–3%.